Improvement of wind turbine performance using a novel tip plate structure. (1st September 2016) - Nobari, M.R.H.; Mirzaee, E.; Nosratollahi, M.
Highlights: Using four different tip plates to improve the wind turbine performance. Study the effect tip plates on reducing the tip blade vortices. Quantitative analysis of wind turbine power increase in the presence of tip plates using 3D numerical simulation. Abstract: In this study, the improvement of a horizontal-axis wind turbine performance is numerically studied using different configurations of tip plates. To do so, we independently develop a 3-D numerical code based on the finite volume method to solve the governing equations including the continuity and Reynolds Averaged Navier-Stokes equations using SST k-ω turbulence model. The NREL Phase VI blade is used as a target blade to suppress the induced drag of the blade tip vortices by the plates attached to the blade tips. The numerical results obtained indicate sixteen percent of power improvement in the two-blade horizontal axis wind turbine for the best tip plate configuration.